Implementasi Metode Multimedia Development Life Cycle (MDLC) dalam Pengembangan Game Edukasi Virtual Tour Kampus Berbasis Roblox Studio - Ruly Dwi Arista; Heri Kurniawan; Fachrid Wadly (Jurnal Nasional Teknologi Komputer, 2026)
Currently, the introduction of the campus environment of still mostly relies on two-dimensional media that limit the freedom of user exploration. As a solution, this research develops an interactive three-dimensional (3D) virtual map using the Roblox Studio platform to present a more modern promotional medium. The system was built using the Multimedia Development Life Cycle (MDLC) method to design a replica of campus buildings equipped with interactive features, such as an information user interface (UI) and the use of yellow almamater attributes for the user avatar. Through this innovation, the university is expected to be able to provide an immersive virtual tour facility, so that the public and prospective students are able to explore the campus layout independently and interactively.